Political morality of the International Monetary Fund - Myers, Robert J., ed. (Transaction Books New BrunswickUS, 1987)
Papers analyze what the IMF is doing and outlines possible means of improving the effectiveness of its operation in the world economy. Contains articles on IMF conditionality, the IMF in Africa, the debt crisis, political dilemas of the IMF, a new role for the IMF, and the future of the Baker plan.